Neurothrombectomy for Acute Ischemic Stroke Across Clinical Trial Design and Technique: A Single Center Pooled Analysis - Jovin, Tudor G.; Desai, Shashvat M.; Aghaebrahim, Amin; Ducruet, Andrew F.; Giurgiutiu, Dan-Victor; Gross, Bradley A.; Hammer, Maxim; Jankowitz, Brian T.; Jumaa, Mouhammad A.; Kenmuir, Cynthia; Linares, Guillermo; Reddy, Vivek; et al. (Frontiers in Neurology, 2020)
Introduction: The practice of endovascular therapy has evolved dramatically over the last 10 years with randomized clinical trials investigating the benefit of thrombectomy in select patient populations based on time of presentation, imaging criteria, and procedural technique. We sought to understand the benefit of thrombectomy in patients treated within the context of a clinical trial at a single academic center. Methods: Patient-level data recorded in case forms and core-lab adjudicated data were analyzed from patients enrolled in RCTs investigating the benefit of endovascular thrombectomy over medical management (IMSIII, MR RESCUE, ESCAPE, SWIFT PRIME and DAWN) between 2007 and 2017 at a single academic referral center. Results: A total of 134 patients (intervention group, n=81; medical group, n=53) were identified across five clinical trials (IMSIII, n=46; MR RESCUE, n=4; ESCAPE, n=24; SWIFT PRIME, n=14; DAWN, n=46). There were no significant differences between the treatment arm and control arm in terms of age, gender, baseline NIHSS, ASPECTS and site of occlusion. Rates of good outcome were superior in the intervention group with early neurological recovery (NIHSS of 0-1 or increase NIHSS of 8 points at 24 hours) at a higher rate of 49% vs 17% (p=<0.001) and higher rates of functional independence (90-day mRS 0-2 of 53% vs 26%, p=0.002). In multivariate logistic regression analysis, lower NIHSS and younger age were predictors of good outcome. There were comparable rates of good outcome irrespective of clinical trial, imaging selection criteria (CTP vs MRI), early versus late time window (0-6 hours versus 6-24 hours) and procedural technique (Merci vs Solitaire/Trevo device). There were no differences in rates of sICH, PH-2 or mortality in the intervention group versus medical group. Conclusions: At a large academic center, the benefit of endovascular therapy over medical therapy is observed irrespective of clinical trial design, patient selection or procedural technique.